2021
DOI: 10.1088/1361-6560/ac246f
|View full text |Cite
|
Sign up to set email alerts
|

A robust elastic net-ℓ 12 reconstruction method for x-ray luminescence computed tomography

Abstract: Objective. X-ray luminescence computed tomography (XLCT) has played a crucial role in pre-clinical research and effective diagnosis of disease. However, due to the ill-posed of the XLCT inverse problem, the generalization of reconstruction methods and the selection of appropriate regularization parameters are still challenging in practical applications. In this research, an robust Elastic net-ℓ1ℓ2 reconstruction method is proposed aiming to the challenge. Approach. Firstly, our approach consists of ℓ1 and ℓ2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the field of DFMT, the distribution characteristics of fluorescence change over time exhibit a certain degree of spatiotemporal continuity and diversity. Additionally, it holds a wealth of structural prior information and internal connections, such as structural sparse regularization prior (Jiang et al 2016, Liu et al 2017, Zhao et al 2021, Guo et al 2022. Hence, the primary challenge in this study is to devise an efficient, suitable and speedy reconstruction method based on these prior knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of DFMT, the distribution characteristics of fluorescence change over time exhibit a certain degree of spatiotemporal continuity and diversity. Additionally, it holds a wealth of structural prior information and internal connections, such as structural sparse regularization prior (Jiang et al 2016, Liu et al 2017, Zhao et al 2021, Guo et al 2022. Hence, the primary challenge in this study is to devise an efficient, suitable and speedy reconstruction method based on these prior knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the quality of images obtained from a reduced number of projections, which is advantageous for rapid biomedical imaging applications, the utilization of compressed sensing (CS) theory has been employed for reconstruction. Various methods, including the L1-TV method [21], robust elastic net-ℓ1ℓ2 method [22], and T-FISTA method [23], have been utilized to achieve this goal. With the utilization of sparsity or group sparsity as a prior, our research team has successfully shown that CB-XLCT has the capability to differentiate between two targets with an edge-to-edge distance (EED) of 0.1 cm by employing two imaging views [24].…”
Section: Introductionmentioning
confidence: 99%